“Sorry. I am what I am. ” - Walton, Chris (Basler Afrika Bibliographien, 2024)
Gordon Jephtas (1943–92) was born into an impoverished, coloured, single-parent family in South Africa. He began piano lessons after being intrigued by the harmonium player at the local church. In his teens he worked as an accompanist with the amateur coloured opera group “Eoan” in Cape Town, then moved to Europe to further his studies. His first big break came in 1972 when the Zurich Opera House appointed him to assist the conductor Nello Santi. Jephtas thereafter established an international reputation as a vocal coach of Italian opera, and Switzerland provided him with a liberal environment where he was free to express his sexuality. Both there and later in the USA, Jephtas worked with the biggest names in the opera world, from Renata Tebaldi to Plácido Domingo, Montserrat Caballé and Luciano Pavarotti. He always longed to be accepted back in South Africa, but his attempts to return culminated each time in disaster because talent and experience meant little in a land where “whiteness” trumped everything. An official offer to be made an “honorary white” merely intensified his inner turmoil. Back in the USA, Jephtas’s professional success was tempered by private misfortune. He died in New York in 1992. This book examines the life and career of Gordon Jephtas through the letters that he wrote home to May Abrahamse, a coloured singer with whom he had worked since his teens. They reveal in unique detail the life and achievements of a remarkable musician, but also the psychological damage wrought upon him by apartheid. Jephtas provides a fascinating case study of a gifted South African abroad, struggling with issues of race and sexuality at the height of the AIDS epidemic.